AUTHENTIC LEARNING THROUGH A MARKET DAY PROGRAM IN KINDERGARTEN: ITS IMPACT ON CHILDREN’S INDEPENDENCE AND SELF-REGULATION - Mawaddah, Khusnatul; Ekowati, Dyah Worowirastri; Syahri, Mohammad (JURNAL EDUSCIENCE, 2026)
Purpose – This study evaluates the Market Day program at TK ABA Percontohan, Bojonegoro Regency, as an authentic learning strategy to foster independence in early childhood using a CIPP-based evaluation framework.Methodology – The study used a qualitative approach. Participants were selected purposively and involved 27 respondents: the principal (n=1), teachers (n=4), and parents/guardians (n=5), while 17 children were observed as research subjects without being interviewed. Data were collected through structured observations during Market Day, semi-structured interviews, and document analysis. Data analysis followed an interactive process of reduction/coding, data display, and drawing and verifying conclusions through source and method triangulation.Findings – Market Day functioned as an authentic learning activity that stimulated children's life skills, including early financial literacy, confidence in social interaction, decision-making based on their allowance, responsibility for their goods and sales booth, and emotional self-regulation (waiting in line, being patient, and accepting consequences). The main challenges were money, numeracy skills—especially when calculating and giving change—differences in children's confidence and communication, queue discipline, and inconsistent parental involvement and product standards. These findings suggest the need for stronger scaffolding to support money-related numeracy.Contribution – This study contributes by providing a holistic CIPP-based evaluation of Market Day, formulating observable indicators of children’s independence in authentic transaction settings, and offering practical recommendations to strengthen scaffolding and program quality in kindergarten and similar early childhood education contexts.